Country profile – Senegal: Gender, climate change, and nutrition linkages - Marivoet, Wim; Diatta, Ampa Dogui; Thomas, Timothy S.; Ferguson, Nathaniel; Bryan, Elizabeth (International Food Policy Research Institute, 2025)
This country brief supports GCAN's goal of integrating gender, climate resilience, and nutrition considerations into policies, interventions, and research by providing policymakers, program officers, and researchers with an analysis of Senegal’s current situation and policy landscape in these areas. In 2019, the agrifood system of Senegal accounted for 36% of total GDP and employed 43% of the total work force. The off-farm components (i.e., processing, trade/transport, food services, and input supply) are slightly more (less) important than primary agriculture in terms of GDP (employment), which implies that labor productivity is higher for off-farm activities. The most important value chains as a percentage of total agrifood system’s GDP are groundnuts (15%), cattle/dairy (14%), and sorghum/millet and fish (both around 11%) (Diao et al. 2023). In part due to important food losses observed during storage and distribution, Senegal’s agrifood system is generally failing to provide nutritious and affordable diets to its population. In fact, total food supplies are dominated by energy-dense food items, with supplies in fruit and pulses amounting to only 55 and 15 grams per capita per day, respectively, resulting in 50% of all Senegalese being unable to afford a healthy diet in 2022.